THE INFLUENCE OF SERVICE QUALITY ON PATIENT SATISFACTION AND LOYALTY IN THE CLINIC: A SYSTEMATIC REVIEW - Wulandari, Nadia; Paramarta, Vip; Purwanda, Eka (CV. Lafadz Jaya, 2024)
This systematic review aims to explore the influence of service quality on patient satisfaction and loyalty in clinics. With the growing need for healthcare services and increasing competition among healthcare providers, understanding the key determinants of patient satisfaction and loyalty becomes crucial. The review analyzed multiple studies on service quality in clinics, focusing on key service dimensions such as reliability, responsiveness, assurance, empathy, and tangibles. These dimensions are critical in forming patient perceptions and determining the overall patient experience. Our findings reveal that service quality significantly impacts patient satisfaction, which in turn fosters loyalty. Satisfied patients are more likely to return to the clinic for future services and recommend it to others. Factors such as the professionalism of healthcare providers, the cleanliness of the facilities, and efficient communication contribute to patient loyalty. However, not all patients react similarly, as individual demographic and clinic-specific factors can influence their responses. This review concludes with recommendations for clinics to enhance service quality and patient-centered care to maintain a competitive edge.